Impact of ocean phytoplankton diversity on phosphate uptake. - Lomas, Michael W; Bonachela, Juan A; Levin, Simon A; Martiny, Adam C (eScholarship, University of California, 2014)
We have a limited understanding of the consequences of variations in microbial biodiversity on ocean ecosystem functioning and global biogeochemical cycles. A core process is macronutrient uptake by microorganisms, as the uptake of nutrients controls ocean CO2 fixation rates in many regions. Here, we ask whether variations in ocean phytoplankton biodiversity lead to novel functional relationships between environmental variability and phosphate (Pi) uptake. We analyzed Pi uptake capabilities and cellular allocations among phytoplankton groups and the whole community throughout the extremely Pi-depleted western North Atlantic Ocean. Pi uptake capabilities of individual populations were well described by a classic uptake function but displayed adaptive differences in uptake capabilities that depend on cell size and nutrient availability. Using an eco-evolutionary model as well as observations of in situ uptake across the region, we confirmed that differences among populations lead to previously uncharacterized relationships between ambient Pi concentrations and uptake. Supported by novel theory, this work provides a robust empirical basis for describing and understanding assimilation of limiting nutrients in the oceans. Thus, it demonstrates that microbial biodiversity, beyond cell size, is important for understanding the global cycling of nutrients.